2020
DOI: 10.1002/anie.202008925
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Structurally Defined Graphene Nanoribbons by Myeloperoxidase and the Photo‐Fenton Reaction

Abstract: As an emerging member of the graphene family, structurally defined graphene nanoribbons (GNRs) have shown promising applications in various fields. The evaluation of the degradability of GNRs is particularly important for assessing the persistence level and risk of these materials in living organisms and the environment. However, there is a void in the study of the degradation of GNRs. Here, we report the degradation behavior of GNRs in the presence of human myeloperoxidase (hMPO) or treated with the photo‐Fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…demonstrated that carboxyl‐functionalized graphene nanoribbons (GNRs) can be efficiently degraded by MPO or photo‐Fenton reaction. The results showed that both MPO and photo‐Fenton reactions degraded GNRs almost completely after 120 h. [ 44 ] Table 1 lists the enzymes studied to date, their source, and the redox potentials of their intermediates during the peroxidase cycle. [ 17,43,45,46 ] Previous studies in this domain have already elucidated these enzymes’ action mechanisms, especially HRP and MPO.…”
Section: Biodegradation Of Carbon‐based Nanomaterialsmentioning
confidence: 99%
“…demonstrated that carboxyl‐functionalized graphene nanoribbons (GNRs) can be efficiently degraded by MPO or photo‐Fenton reaction. The results showed that both MPO and photo‐Fenton reactions degraded GNRs almost completely after 120 h. [ 44 ] Table 1 lists the enzymes studied to date, their source, and the redox potentials of their intermediates during the peroxidase cycle. [ 17,43,45,46 ] Previous studies in this domain have already elucidated these enzymes’ action mechanisms, especially HRP and MPO.…”
Section: Biodegradation Of Carbon‐based Nanomaterialsmentioning
confidence: 99%
“…[ 154 , 155 ] This process transforms epoxy groups of GFMs to more energetically favorable carbonyl groups and results in the rupture of underlying C—C bonds. [ 154 , 156 , 157 ] Finally, GFMs are digested into oxidized polycyclic aromatic hydrocarbons (PAHs) and carbon dioxide, [ 155 , 158 , 159 ] and exported from macrophages via exocytosis. The dispersed large GFMs (>250 nm) will trigger invagination of membrane and be engulfed into phagosome vesicles of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…HOCl produced by peroxidase from H 2 O 2 could be a major cause of the biodegradation of carbon nanomaterials [ 149 , 150 , 151 ]. Several studies have confirmed that recombinant hMPO is able to degrade single-layer and multi-layer GOs [ 153 , 154 ], and that the degradation products are non-toxic [ 155 ]. Through other studies, researchers have shown that graphene-based materials can be degraded by hMPO [ 153 ], recombinant eosinophil peroxidase [ 156 ], and HRP [ 153 , 157 ].…”
Section: Toxicitymentioning
confidence: 99%